2016
DOI: 10.2147/ceor.s95662
|View full text |Cite
|
Sign up to set email alerts
|

Short- and longer-term health-care resource utilization and costs associated with acute ischemic stroke

Abstract: ObjectivesThe mean lifetime cost of ischemic stroke is approximately $140,048 in the United States, placing stroke among the top 10 most costly conditions among Medicare beneficiaries. The objective of this study was to describe the health-care resource utilization and costs in the year following hospitalization for acute ischemic stroke (AIS).MethodsThis retrospective claims analysis quantifies utilization and costs following inpatient admission for AIS among the commercially insured and Medicare beneficiarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 13 publications
2
51
0
3
Order By: Relevance
“…Despite the evidence that long-term costs are substantial, few studies have quantified short-term and long-term direct costs [23,24]. Studies that systematically evaluated readmission after stroke have shown that patients with a more severe form of the disease have higher readmission rates both at 30 and 90 days [25,26]. Also, re-hospitalizations are more frequent in the elderly, one of the studies indicating relatively high readmission rates, 25-39% within 30 days [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evidence that long-term costs are substantial, few studies have quantified short-term and long-term direct costs [23,24]. Studies that systematically evaluated readmission after stroke have shown that patients with a more severe form of the disease have higher readmission rates both at 30 and 90 days [25,26]. Also, re-hospitalizations are more frequent in the elderly, one of the studies indicating relatively high readmission rates, 25-39% within 30 days [25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that systematically evaluated readmission after stroke have shown that patients with a more severe form of the disease have higher readmission rates both at 30 and 90 days [25,26]. Also, re-hospitalizations are more frequent in the elderly, one of the studies indicating relatively high readmission rates, 25-39% within 30 days [25]. In another recent study on 307,887 patients with insurance in the public health system who suffered an ischemic stroke, 14.4% of patients had readmissions within 30 days after discharge [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…7 lifetime cost of ischemic stroke per person, which includes inpatient care, rehabilitation, and follow-up care, is estimated at $140,048 in the United States. 9 The total annual direct costs were estimated at €26.6 billion in 2010 for the European Union (EU) plus Iceland, Norway, and Switzerland. 10 The economic burden caused by stroke has not been well explored in developing countries; according to estimates by the World Health Organization (WHO), India, for example, lost $8.7 billion in 2005 due to coronary heart disease (CHD), stroke, and diabetes.…”
Section: Disabilitymentioning
confidence: 99%
“…Model assumptions, resource utilization, and unit cost data were acquired from numerous sources as described in Table 1. The latest healthcare expenses accounting for treatment and physician costs, longterm care, as well as first-year medical device costs were primarily derived from RED BOOK and the Centers for Medicare & Medicaid Services, as well as several other relevant published data sources (Table 1) 17,18 . For the purpose of this model, outcomes were expressed as costs using 2018 USD ($) per quality-adjusted life-year (QALY).…”
Section: Model Structure and Overviewmentioning
confidence: 99%